2013
DOI: 10.1590/s0102-86502013000600002
|View full text |Cite
|
Sign up to set email alerts
|

Experimental ovarian transplantation on stomach for bone repair in ovariohysterectomized rabbits

Abstract: PURPOSE:To evaluate the bone repair process in ovariohysterectomized rabbit submitted to an ovarian transplant to stomach that may supplying some quantity of estrogen occurs to improve bone healing. METHODS:In 20 female rabbits three holes of 1, 2 and 3mm diameter in tibial shaft were made and after that all animals received OHE through a ventral incision and they were randomly divided into two groups of ten rabbits each. In group one, animals received one of their self-ovaries that transplanted on serosal lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Therefore, to evaluate the biological effect of samples on bone repair, we used tibial defects in rabbits considering the animal size, low cost, and easy management, with a considerable scientific background supporting their use to study biomaterials and the similarity with the mineral bone density from humans [38]. The non-critical bone defect of 2 mm diameter in tibiae followed the ISO 10993-6/2016 since a previous study showed similar repair of a tibial defect of 1.0, 2.0, and 3.0 mm after 45 d [39], supporting the use of 2.0 mm diameter defect. The micrometric spheres (425-600 µm) dispersed quickly in the surgical site, mainly the HA90 and HA5, quickly fragmented by the alginate dissolution, the strong interaction of particles with interstitial fluid and local cells with clastic activities present at the site of perforations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to evaluate the biological effect of samples on bone repair, we used tibial defects in rabbits considering the animal size, low cost, and easy management, with a considerable scientific background supporting their use to study biomaterials and the similarity with the mineral bone density from humans [38]. The non-critical bone defect of 2 mm diameter in tibiae followed the ISO 10993-6/2016 since a previous study showed similar repair of a tibial defect of 1.0, 2.0, and 3.0 mm after 45 d [39], supporting the use of 2.0 mm diameter defect. The micrometric spheres (425-600 µm) dispersed quickly in the surgical site, mainly the HA90 and HA5, quickly fragmented by the alginate dissolution, the strong interaction of particles with interstitial fluid and local cells with clastic activities present at the site of perforations.…”
Section: Discussionmentioning
confidence: 99%